The Relationship Between Nutritional Status and Sexual Satisfaction in Premenopause Women in The Working Area of Tamalanrea Jaya Primary Health Center - Nurhidayat Triananinsi; Hairuddin Hairuddin; Jumiati Jumiati (Jurnal Gizi dan Kesehatan Keluarga, 2023)
Premenopause is a phase in the aging process when a woman undergoes the transition from the reproductive stage to the non-reproductive stage, which occurs before menopause. During this period, there are endocrine, biological, and clinical changes, signaling the onset of menopause and covering the first year or twelve months after menopause. The nutritional status is directly assessed using anthropometric measurements, such as height and weight. The normal BMI (Body Mass Index) is considered to be between 18.5 and 25 kg/m2. Sexual satisfaction in premenopausal women in this study refers to the discomfort in the aspect of female sexuality caused by vaginal thinning due to decreased estrogen levels, resulting in reluctance to engage in sexual activities. This research is conducted using an Analytical research design with a Cross-Sectional Study approach, which focuses on measuring independent and dependent variables simultaneously. The method used for this study is Observational with a Cross-Sectional Study approach to examine the relationship between Nutritional Status and Sexual Satisfaction in Premenopausal women at Tamalanrea Jaya Primary Health Center in 2018. The population of this study consists of all mothers, with a sample size of 30 people, selected through Purposive Sampling technique. The research results indicate that there is a significant relationship between nutritional status and sexual satisfaction with a value of p = 0.0001. The study also shows that there is a relationship between nutritional status and sexual satisfaction in premenopausal women with a value of p = 0.012. (p ≤ 0.05)